ANALYSES AND VALIDATION OF MEASURED METOCEAN DATA IN TIME AND FREQUENCY DOMAINS FOR MALAYSIAN WATERS - VANNAK, DUONG (2013)
In this research, the data of wave height and wind speed are collected from metocean data of the three existing oil fields in South China Sea - the Malay basin, Sarawak basin and Sabah basinby getting extreme value and significant data for analysis. The data consists of measured data which were recorded from year 1999 until 2008.The data have been used for studying the planning of projects, the design of structure and the maintenance of existing platforms to suit local conditions and to minimizethe risks. The offshore structures are particularly at risk with any extreme motions initiated by wind and wave.